Effect of autotransplantation of fibroblasts and keratinocytes with fibroblasts mixture in the area of skin radiation burn on the dynamics of metallothioneins, ubiquitin and p53 genes expression - Алтухова, Л. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 1970)
There has been studied gene expression of metallothioneins 1–5, ubiquitin В, p53 protein and their products in the area of the 3rd degree X-ray skin burn in guinea pigs at daily 35-day autotransplantation of ﬁbroblasts and a mixture of fibroblasts and keratinocytes started immediately after exposure. It has been shown that in the burn zone gene expression of metallothioneins 1–5, ubiquitin B and content of these proteins continually decreases, and gene expression of p53 protein and its content increase. Introduction of autofibroblasts or mixtures thereof with keratinocytes into the burn zone increases metallothioneins 1–5 and ubiquitin B gene expression and content of these proteins (to a greater degree at cell mixture administering), while reducing p53 protein gene expression and normalization of its content.